A Forced Choice Version of the MSCS and How It Discriminates Campus Leaders and Nonleaders - Steger, Joseph A.; Kelley, Winslow B.; Chouintere, Gregory; Goldenbaum, Arnold (Academy of Management Journal, 1975)
Use of a forced choice version of the Miner Sentence Completion Scale showed close agreement with the original MSCS. A validity study demonstrated that the new version could differentiate leaders from nonleaders. The revised version, while just as effective a scale as the original, was found to be more efficient to use.